Biomaterials for microfluidic technology. (1st March 2022) - Chen, Zehao; Lv, Zhendong; Zhang, Zhen; Zhang, Yuhui; Cui, Wenguo
Abstract: Micro/nanomaterial-based drug and cell delivery systems play an important role in biomedical fields for their injectability and targeting. Microfluidics is a rapidly developing technology and has become a robust tool for preparing biomaterial micro/nanocarriers with precise structural control and high reproducibility. By flexibly designing microfluidic channels and manipulating fluid behavior, various forms of biomaterial carriers can be fabricated using microfluidics, including microspheres, nanoparticles and microfibers. In this review, recent advances in biomaterials for designing functional microfluidic vehicles are summarized. We introduce the application of natural materials such as polysaccharides and proteins as well as synthetic polymers in the production of microfluidic carriers. How the material properties determine the manufacture of carriers and the type of cargoes to be encapsulated is highlighted. Furthermore, the current limitations of microfluidic biomaterial carriers and perspectives on its future developments are presented.